KEMAMPUAN MENULIS SURAT PRIBADI SISWA KELAS VII SMP NEGERI 16 PEKANBARU - Christine Pasaribu; M. Nur Mustafa; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study examines the ability to write personal letter of grade VII students of SMP Negeri 16 Pekanbaru. The purpose of this study is to identify the level of personal writing skills of grade VII students of SMP Negeri 16 Pekanbaru and to identify whether there is any difference in personal letter writing skills of the seventh grade students of SMP Negeri 16 Pekanbaru. This research has population 110 and sample 86. The data of this research that is test result of student's answer in doing self writing skill test of class student of class VII SMP Negeri 16 Pekanbaru. The test used is a story essay test. The tests instruct students to write personal letters on the topics provided and take note of parts of personal letters, spelling and punctuation (capital letters, periods, commas, exclamation points and question marks). The data were analyzed by quantitative descriptive method through test to know the level of personal writing ability of kels VII students of SMP Negeri 16 Pekanbaru, one way ANOVA test to know the difference of personal writing skill of class VII students of SMP Negeri 16 Pekanbaru between sample group. the results of this study in the form of personal letter writing skills of students in grade VII SMP Negeri 16 Pekanbaru classified as low with average value.Keywords: Ability, Writing, Private Letter, Student